2022
DOI: 10.1111/ctr.14590
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of diabetic patients with end‐stage heart failure listed for heart transplantation: A propensity‐matched analysis

Abstract: Background:We investigated the current trends and outcomes of diabetic patients listed for heart transplants in the U.S. and provided a method for risk-stratification. Methods:Using data from the United Network for Organ Sharing (UNOS), we identified heart failure patients listed for heart transplants between 2010 and 2019. Diabetic patients were propensity-matched with non-diabetics, and waitlist mortality as well as post-transplant graft survival were compared between the two groups. Further risk-stratificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several epidemiological studies had previously indicated that recipients with T2D undergoing HT differ from other types of patients [ 7 ]. A recent study reported that patients with diabetes experienced poorer graft survival following transplantation (HR 1.17; 95% CI 1.08–1.26, P < 0.001), although the authors scored graft survival to further stratify the risk of patients with diabetes and found that graft survival was similar in low-risk diabetic patients and non-diabetic patients (HR 0.91; 95% CI 0.82–1.01) [ 23 ]. In our study, individuals with T2D were less likely to have pneumonia and Gram-negative bacterial infections or undergo hemodialysis, ECMO, and tracheostomy procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies had previously indicated that recipients with T2D undergoing HT differ from other types of patients [ 7 ]. A recent study reported that patients with diabetes experienced poorer graft survival following transplantation (HR 1.17; 95% CI 1.08–1.26, P < 0.001), although the authors scored graft survival to further stratify the risk of patients with diabetes and found that graft survival was similar in low-risk diabetic patients and non-diabetic patients (HR 0.91; 95% CI 0.82–1.01) [ 23 ]. In our study, individuals with T2D were less likely to have pneumonia and Gram-negative bacterial infections or undergo hemodialysis, ECMO, and tracheostomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A love plot was generated to visualize how populations become comparable after PSM. PSM has been previously used by other authors to compare the outcomes of HT according to clinical conditions and procedures [23][24][25][26][27][28][29][30].…”
Section: Propensity Score Matchingmentioning
confidence: 99%